Ptarmigan hunting restrictions: Effects on hunters' opinions and harvest. Issue 7 (1st August 2017) - Breisjøberget, Jo Inge; Storaas, Torstein; Odden, Morten
ABSTRACT: In Norway, willow ( Lagopus lagopus ) and rock ptarmigan ( Lagopus muta ) populations and harvests have declined during the last few decades, and the 2 species are considered as near threatened on the Norwegian Red List. The Norwegian State‐Owned Land and Forest Enterprise (Statskog) is a main provider of ptarmigan hunting on public lands, and has recently introduced harvest restrictions in Nordland County. We investigated the relationship between hunters' opinions and the effects of restrictions on hunters and ptarmigan harvest using online structured questionnaires (2012, n = 570) and bag reports (2009–2011, n = 8, 795). A majority of hunters (66%) supported harvest restrictions, and 89% were willing to shoot fewer birds to increase population size. However, opinions towards specific management alternatives were more negative and disparate. Residency of the hunters (local or non‐resident) was the most influential factor on hunter opinions, and this reflected a tendency to approve of restrictions with the smallest effect on their own hunting practice. Our study indicates that access and the opportunity to hunt are more important to hunters than bag size. Daily and annual hunting bags were small, averaging 1.7 and 5.8 ptarmigan, respectively, and the daily bag limit of 4 birds was reached during 5.8% of hunting days. A harvest reduction of 50% implied a daily bag limit of 1 bird and a seasonal bag of 4, which were lower than what hunters found as acceptable. Hence, although hunter opinions may provide useful guidelines for the development of management practices, their opinions need to be evaluated for the actual effects they may have on the game populations. © 2017 The Authors. Journal of Wildlife Management Published by Wiley Periodicals, Inc. Abstract : We report that although most hunters were positive to ptarmigan hunting restrictions in general, opinions towards specific management alternatives were more negative and disparate. Daily and annual hunting bag limits of only 1 and 4 birds, respectively, would have been needed to obtain a harvest reduction of 50%, and this was far lower than hunters found acceptable.